1996
DOI: 10.1111/j.1471-6402.1996.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Spatial Training Erase the Gender Differences on the Water-Level Task?

Abstract: Spatial training has been only modestly effective at improving the performance of adolescents and adults on the water-level task. Based on previous findings with the task, a self-discovery training procedure was developed that involved having participants proceed from easier to more difficult problems along a dimension of increasingly greater competing perceptual cues. The training was effective in (a) eliminating the gender differences on the drawing task, and (b) significantly improving females' knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 24 publications
3
36
1
Order By: Relevance
“…Perhaps the male advantage on spatiotemporal tasks can be partially explained by the use of visual imagery in these tasks. We also note that the size of the sex difference on many tests of visuospatial processing can be reduced with training (e.g., Vasta & Gaze, 1996). Converging support for these conclusions comes from a study of gifted students who were either in the top 20% in spatial ability or the top 20% in verbal ability.…”
Section: Discussionmentioning
confidence: 65%
“…Perhaps the male advantage on spatiotemporal tasks can be partially explained by the use of visual imagery in these tasks. We also note that the size of the sex difference on many tests of visuospatial processing can be reduced with training (e.g., Vasta & Gaze, 1996). Converging support for these conclusions comes from a study of gifted students who were either in the top 20% in spatial ability or the top 20% in verbal ability.…”
Section: Discussionmentioning
confidence: 65%
“…The effects of training were similar for males and females; that is, both groups benefited about equally from the training, and there was little evidence that the gap was closed or widened by training. Vasta, Knott, and Gaze (1996), however, showed that the difference could be eliminated by carefully conceptualized training. Unfortunately, most school curricula contain little or no emphasis on spatial learning.…”
Section: Training Studiesmentioning
confidence: 99%
“…These findings suggest that it may be specific angular relations between the water line and the bottle side that are learned rather than a generalized representation of invariant horizontality (Liben, 1991b). On the other hand, some training studies have shown positive effects of practice from mental rotation games or water-level stimuli to later performance on paper-and-pencil tests with different stimuli (De Lisi & Wolford, 2002;Okagaki & Frensch, 1994;Vasta, Knott, & Gaze, 1996). More generally, Baenninger and Newcombe (1989) summarized spatial training effects by a meta-analysis of training studies that were aimed at examining whether the sex differences in spatial performance are amenable to instruction.…”
Section: Can Spatial Thinking Be Improved?mentioning
confidence: 99%